Rozwój oka u dzieci. Część II. Refrakcja oka - Lachowicz, Ewelina; Czepita, Damian (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The aim of this article is to introduce and elaborate on changes of eye refraction during growth of the eyeball based on available literature. Material and methods: All the data in the article comes from studies performed on children from different age groups. In some studies children were divided to different gender groups with some parameters being analyzed separately. Total refraction, corneal and lens power was defined. The theory concerning process to reach emmetropia was presented. Results: The eyeball dimensions undergo intensive change with age. During this time a period of fast and slow growth of the eye can be observed. Axial length of the eye, corneal curvature, depth of anterior chamber, lens’s structure and curvature are developed. Due to the dynamic growth of the eyeball, changes in eye refraction also occur. A correct anatomically and functioning eye is called emmetropic. Changes of eye refraction mostly occur during the early years of life and afterward stabilize. Refraction depends on the increase of axial length and changes in corneal and lens power. The process to reach emmetropia in the eye is based on local feedback mechanism. Emmetropia is the result of both passive and active processes during the period of growth. Total refracting power is reduced after birth to maintain an emmetropic state in adults. Mean corneal and lens power decreased with age. Girls tend to have steeper corneas, stronger crystalline lenses and shorter eyeballs compared with boys. Refraction of small eyeballs in children is more powerful than in adults. Conclusions: Based on available literature it is difficult to conclusively indicate the standards of refraction during growth in children and teenagers. In order to establish these parameters, further examinations on a representative group of children and teenagers is necessary.